Health Care Beliefs and Practices among Atas in Canggohob, Mabinay, Philippines - Real, Don Vicente C.; Aniñon, Elsie C.; S. Aller, Francy; Q. Resoor, Nonale; Englis, Andrea Luz (European Journal of Applied Sciences, 2023)
The study examined the healthcare beliefs and practices among atas in Barangay Canggohob, Mabinay, Philippines. There were 25 respondents, 10 of them were Ata women who had experienced pregnancy and 1 tribal chieftain and 14 tribal healers. The qualitative-phenomenological research method was used in utilizing focus group interviews, participant observation, and video documentation. Ethical approval was secured, and the participants consented to the conduct of the research. The findings revealed that atas still believed that sickness was caused by weather and supernatural forces of nature. The diversity of herbal medicines and the preparation had cultural importance to Atas' different stages of life and healing practices. There were not much of healthcare practices during puberty, adolescence, and adulthood except for menstrual beliefs and circumcision which were relative to their cultural views. Moreover, atas perceived that technology, media, modernization, and medical missions and outreach programs disconnected them from their cultural identity, yet, they had been part of society's mainstream. In doing so, a comprehensive health program is initiated by the Municipality of Mabinay which will address the unique health practices of Ata mothers and other members of the tribal group, as a part of the Annual Investment Plan and a mandate of Republic Act No. 8371 or the Indigenous People's Rights Act of 1997. Towards this end, a further study on the culture of atas through ethnographic background immersion be further pursued to develop a culturally congruent nursing care model that will streamline evidence-based practices for atas.